A Mizoroki-Heck Coupling attempt with Pd(OAc)2 as catalyst and amine as base in the absence of Ligand - Welem L Turupadang (Jurnal Akuatik, 2021)
An attempt to stepwise synthesis Mizoroki-Heck Coupling (E)-1,2-diphenylethene has been done in an inert atmosphere from olefin (styrene) and bromobenzene. The experiment involved palladium acetate as the catalyst and triethylamine as a base along with DMF as solvent